Investigation on refrigerant transport by capillary effect with fleeces in an evaporator for a high temperature cooling machine. (September 2018) - Holbein, Benedict; Schulenberg, Thomas
Highlights: An evaporator design using passive capillary transport is presented. Capillary rise in fleeces is described theoretically. Fleece properties are determined experimentally. Fleece supported wetting is observed with evaporation experiments. Abstract: The work described in this paper is part of development of a compact cooling machine for electronics in well environments with ambient temperatures above 200  °C. It includes an evaporator, a compressor and a condenser such that the cooling machine can be operated permanently. The evaporator is designed as a capillary evaporator. Instead of metal or polymer wicks, different fleece materials based on cellulose and wool have been investigated regarding capillary wetting on heat transfer surfaces. Characteristic fleece properties have been determined experimentally. The tests include effects supporting the wetting rise, such as multiple layers, compressed layers, pre-wetted fleeces and increased temperature. Results of evaporation tests show the functionality of the evaporator principle and confirm sufficient cooling effect. The presented work can serve as basis for further investigation of wetting under evaporation influence and for optimization of functionality of evaporator design using passive capillary wetting with fleece materials.